Changes in the provision of health care in South Africa - J. Luiz; M. Wessels (South African Journal of Business Management, 2004)
Health care in South Africa is undergoing substantial changes with rising pressure on both the public and private sectors. Medical inflation has been soaring rendering healthcare increasingly unaffordable and medical schemes have had to adapt their traditional business models. This paper looks at the current structure of the healthcare market; it examines the new legislation introduced by government, and assesses future directions of healthcare in South Africa.
Keywords: 650